Estrutura de comunidades e dinâmica da regeneração natural de floresta estacional decidual no Sul do Brasil - Callegaro, Rafael Marian (2015)
The distribution of arboreal and shrub species is related to different environmental conditions. The general goal of this study was to evaluate the influence of environmental factors in structure of communities and dynamics of the natural regeneration in Deciduous Seasonal Forest stretch, located in Quarta Colônia State Park, Agudo, RS, Brazil. The specific goals were to differentiate the structure and floristic of clusters (floristic groups) of the arboreal component, determining which environmental variables influenced the forest structure, identifying what changes have occurred in a year of natural regeneration monitoring and identifing which variables limited or facilitated the establishment of arboreal and shrub populations. Three levels of inclusion were used for sampling forest communities: arboreal component (diameter at breast height (DBH) ≥ 5 cm), sampled in 33 plots of 20 m x 20 m (1.32 ha); natural regeneration Class I (1 cm ≤ DBH < 5 cm), sampled in sub-plots of 4 m x 10 m (0.132 ha); and natural regeneration Class II (DBH < 1 cm and height ≥ 20 cm), sampled in sub-plots of 4 m x 2.5 m (0.033 ha). Cluster II showed the highest average diameter (40.0 cm) and the basal area (1.353 m2 plot-1= 33.825 m2 ha-1). The highest richness (70 species) occurred in Cluster I. The two clusters showed negative exponential diameter distribution, common to the forests with self-regeneration capacity. The species with more developed structure in natural regeneration was Trichilia elegans, Cupania vernalis and Actinostemon concolor, and Trichilia clausseni, Nectandra megapotamica and Allophylus edulis in arboreal component. The species of arboreal component showed association with relief, chemical and textural properties of soil and canopy characteristics, of which only the texture was not related to the regenerating species. The species with the highest value of Natural Regeneration Relative (RNR) kept their posts at the end of the measurements. Different values of Ingrowth Rate (IR), Mortality (MR) and Regeneration (RR); and height growth were detected. For example, the species Myrsine umbellata (TI = 58.3%; TM = 100%) and Annona rugulosa (TM = 37.5%; TM = -37.5%) have excelled in relation to the number of individuals fluctuations, while Baccharis sp. (73.3 cm) and Cabralea canjerana (2.5 cm) showed antagonistic values of height growth. Such changes have been influenced by ecological aspects, light dependence and dispersal strategy, and variables such as thickness (height) of accumulated litter and exposure of relief. The analysis of environmental correlations of the most abundant species indicated, for example, that Actinostemon concolor and Sorocea bonplandii were tolerant to shallow soils, with higher levels of stoniness, recurrent situation in forests of edge of the Southern Plateau, while Cupania vernalis and Nectandra megapotamica were correlated negative with these variables. The different relationships observed show that the use of shrub and tree species in ecological restoration should be based on the analysis of potentially favorable or limiting environmental variables.